2019
DOI: 10.1111/aor.13483
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the flow downstream of a dysfunctional bileaflet mechanical aortic valve

Abstract: Mechanical heart valve replacement is the preferred alternative in younger patients with severe symptomatic aortic valve disease. However, thrombus and pannus formations are common complications associated with bileaflet mechanical heart valves.This leads to risks of valve leaflet dysfunction, a life-threatening event. In this experimental study, we investigate, using time-resolved planar particle image velocimetry, the flow characteristics in the ascending aorta in the presence of a dysfunctional bileaflet me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The axial velocity pattern that develops downstream of the valve (Figures 6 and 7) is qualitatively comparable with that reported by De Vita et al 35 and Darwish et al 39 The overall flow physics predicted are similar to the results reported and discussed by Darwish et al, 39 who performed experiments for pulsatile flows in Saint-Jude BMHVs.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The axial velocity pattern that develops downstream of the valve (Figures 6 and 7) is qualitatively comparable with that reported by De Vita et al 35 and Darwish et al 39 The overall flow physics predicted are similar to the results reported and discussed by Darwish et al, 39 who performed experiments for pulsatile flows in Saint-Jude BMHVs.…”
Section: Resultssupporting
confidence: 87%
“…Further, viewing WSS profiles for both models of blood, it is seen that low and oscillating WSS occurs in the wall of the valve, particularly in the sinus of Valsalva, and hence this region is susceptible to atherogenesis. 39,43,44 Obviously the WSS of the non-Newtonian flow is higher than that of the Newtonian flow due to the shear-thinning effect of blood. The negative values in WSS indicate flow recirculation and stagnation.…”
Section: Resultsmentioning
confidence: 99%
“…For the isolated 100% leaflet dysfunction at different flow rates, the Vpeak value increased from 0.84 m/s to 1.94 m/s (127% increase), and the TPGmean value increased from 1.42 mmHg to 6.47 mmHg (350% increase). Moreover, the DVI and EOA were shown to be the less flow-dependent parameters [ 19 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using cardiac simulators, a set of in vitro studies investigated blood flow behavior downstream of BMHV in terms of level of turbulence, shear stress, and coherent structure. Clinically related echo Doppler parameters, such as EOA and Transvalvular pressure gradient, were also explored [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed Darwish et al of Concordia University, Montreal, Canada reported on the flow downstream of a dysfunctional bileaflet mechanical aortic valve. Several configurations of leaflet dysfunction were investigated and the induced flow disturbances in terms of velocity fields, viscous energy dissipation, wall shear stress, and accumulation of viscous shear stresses.…”
Section: Valves and Vascular Supportmentioning
confidence: 99%